Al-Tafkīr ḥaul Makānah al-Mar’ah bi Indūnīsiyā baḥth fī Mawqif al-Islām min al-Ḥarkāt al-Nisā’īyah fī al-Qarnayn al-Tāsi’ ‘Ashr wa al-‘Ishrīn al-Milādiyīn - Munawwaroh, Junaidah (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1999)
the discourse concerning feminism in Indonesian Muslim society is relatively recent. The emergence of such a movement only goes back to the early twentieth century, when R.A Kartini, a daughter of Jepara Resident, struggled for an equal position for man and women in public life. it seems that the movement has tried to respon a particular challenge faced by most women in the Dutch-East Indies who have been discriminated againts and denied access to education. as the movement speards, the discourse on gender rises to become an important issue among muslims in Indonesia, particularly in academic sphere. It grows rapidly with more extensive and subtantial topics of discussion.DOI: 10.15408/sdi.v6i1.748